The Effect of Foreign Term Structure of Interest Rates on Finnish Stock Market - Jokinen, Roni (My University, 2018)
This thesis researches the effect of foreign term structure of interest rates’ in predicting stock market index returns in Finland. A market timing “probit” model will be utilised to invest in stock index of Finland when the probability of a recession in the following month is low. When the model produces a high probability of a recession in the following month, the position will be switched to less risky assets which in this thesis is the 3-month Finnish government bond. The previous literature suggests that the term structure is a viable tool to predict recessions from 1960s to present day. The approach has been transferred to account for possible stock market returns. It has been found that predicting stock market returns with the term structure interest rates is able to generate abnormal returns compared to the stock market index. To further investigate the impact of United States, the yield curve has been found to be able to generate abnormal returns when investing in foreign stock markets. This thesis takes the Finnish perspective into consideration. The preceding literature studied the effect of United States’ yield curve on other countries. This thesis studies the United States yield curve in tandem with Finland’s close economic partners Sweden and Germany. The results produce robust results in the Finnish stock market in the sample period 1987-2017. The thesis studies the term structure of interest rates and the transmission and correlation of global stock markets. The results might prevent an investor generating losses in Finnish stock market declines and thus the contribution is strictly tied to an investor in the Finnish stock market.
Keywords: Term Structure of Interest Rates; Recession; Market Timing; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|